Application of glucose derived magnetic solid acid for etherification of 5-HMF to 5-EMF, dehydration of sorbitol to isosorbide, and esterification of fatty acids - Thombal, Raju S.; Jadhav, Vrushali H. (Tetrahedron Letters, 2016)
In this study, the catalytic activity of Glu-Fe3O4-SO3H was evaluated for three acid catalyzed reactions: etherification of 5-hydroxymethylfurfural (5-HMF) to 5-ethoxymethylfurfural (5-EMF) in ethanol, dehydration of sorbitol to isosorbide, and esterification of fatty acids with good yields and selectivity. Moreover, the catalyst can be easily separated from the reaction with an external magnetic force and reused at least five times without a significant decrease in catalytic activity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: dehydration; Esterification; etherification; Magnetic